DEVICE FOR MANUFACTURING POWER STORAGE MODULE AND METHOD FOR MANUFACTURING POWER STORAGE MODULE - MORI Takeharu; KAWABATA Yoshikatsu; KINUGAWA Tatsuya; HIRAMATSU Yuki (2024)
A device (100) for manufacturing a power storage module comprises: a sensor (C4) that detects a third electrode unit (62) subject to conveyance; a sensor (C5) that detects the third electrode unit (62) subject to lamination; and an adjustment mechanism (G5). The sensor (C4) detects the third electrode unit (62) held by a hand part (H4), and the sensor (C5) detects the third electrode unit (62) placed on a stage (T5). The adjustment mechanism (G5) adjusts the relative position of the third electrode unit (62) by moving the stage (T5) on the basis of the detection result from the sensor (C4) and the detection result from the sensor (C5). Le dispositif de fabrication de module de stockage (100) de l'invention est équipé : d'un capteur (C4) qui détecte une troisième unité électrode (62) constituant un objet à transporter ; d'un capteur (C5) qui détecte une troisième unité électrode (62) constituant un objet à stratifier ; et d'un mécanisme d'ajustement (G5). Le capteur (C4) détecte la troisième unité électrode (62) maintenue par une partie saisie (H4), et le capteur (C5) détecte la troisième unité électrode (62) posée sur une plateforme (T5). Le mécanisme d'ajustement (G5) ajuste la position relative de la troisième unité électrode (62) par déplacement de la plateforme (T5) sur la base des résultats de détection du capteur (C4) et des résultats de détection du capteur (C5). 蓄電モジュール製造装置（１００）は、搬送対象である第３電極ユニット（６２）を検出するセンサ（Ｃ４）と、積層対象である第３電極ユニット（６２）を検出するセンサ（Ｃ５）と、調整機構（Ｇ５）と、を備える。センサ（Ｃ４）は、ハンド部（Ｈ４）に保持された第３電極ユニット（６２）を検出し、センサ（Ｃ５）は、ステージ（Ｔ５）に載置された第３電極ユニット（６２）を検出する。調整機構（Ｇ５）は、センサ（Ｃ４）による検出結果とセンサ（Ｃ５）による検出結果とに基づいてステージ（Ｔ５）を移動させることにより、第３電極ユニット（６２）の相対位置を調整する。